Определение структуры информационного потока на базе «рубрикатора тематических интересов НИИ» для главной справочной картотеки НИИ - Варнене, Регина (Knygotyra, 1983)
This article is devoted to the problem of organizing the information sources for the Principle information card index. It presents an analysis of the documentary flow in galvanotechnics. Investigations were carried out in following directions: — profile contents study, i e. definition of the inter-branch information, — documentary flow groop definition by the sign of genre, — concentration-distribution study of publications in galvanotechnics in Soviet and foreign periodicals, — quantitative study of augmentation of information sources in galvanotechnics, — study of information receiving ways. Index of Soviet and foreign periodicals consulted by researchers of Institute of Chemistry and Chemical Technology was compiled as a result of this study. It systemizes bibliographical entries and presents the percentage of researchers having pointed out the given periodicals, index of “Rubricator of main Soviet information publications” and ways periodicals are racieved. Data obtained in the course of preliminary investigation are of great importance for correct organization of documentary flow of the Principal information card index.